Governing Cross-Border Cyber Threat Intelligence Sharing for Maritime Security Resilience in the Strait of Malacca - Suhirwan Suhirwan (Journal of Contemporary Governance and Public Policy, 2026)
The Straits of Malacca and Singapore are among the most strategically important maritime chokepoints in the global trading system. Although conventional threats such as piracy have been managed through regional cooperation, the rapid digitalisation of ports, vessel traffic systems, and naval command infrastructures has created new hybrid cyber-physical vulnerabilities. Despite recurring cyber incidents between 2020 and 2025, no institutionalised real-time cross-border Cyber Threat Intelligence (CTI) mechanism has emerged among Indonesia, Malaysia, and Singapore. This study examines the puzzle of institutional inertia under growing threat interdependence and its implications for SDG 9, Target 9.1 on resilient infrastructure, and SDG 17, Targets 17.16 and 17.17 on knowledge-sharing and effective public-private partnerships. Drawing on 18 semi-structured interviews and qualitative analysis of policy documents from 2020 to 2025, the study identifies three governance bottlenecks: legal-institutional ambiguity, sovereignty-related political constraints, and technical-operational interoperability gaps. Building on Regional Security Complex Theory and regime complexity scholarship, the article theorises Cooperative Sovereignty as a middle-ground governance modality between supranational integration and sovereignty-maximising bilateralism. It proposes the Malacca Cyber Intelligence Node (MCIN) as a federated, sovereignty-compatible mechanism for structured cyber threat signalling while preserving national control over data. The study contributes to governance scholarship and offers actionable pathways for strengthening maritime cyber resilience in sovereignty-sensitive regions.